Analysis of Parent Satisfaction Towards Early Childhood Education Services in Tirtajaya District - Rivo Panji Yudha; Nata Priatna (Kirana Publisher (KNPub), 2024)
This research aims to analyze the satisfaction level of parents of students with the educational services provided by Early Childhood Education (PAUD) institutions in Tirtajaya District, Karawang Regency. The study focuses on several key aspects of educational services, including the quality of educators, facilities and infrastructure, management, content and process of education, and the level of achievement in children's development. A quantitative approach was employed, utilizing survey methods to collect numerical data from a large number of respondents using questionnaires. The survey method was chosen to describe quantitatively certain phenomena by presenting average scores, deviations, graphs, and to make predictions and estimates based on identified analyses and models. The research was conducted in PAUD institutions across Tirtajaya District, Karawang Regency, during the 2023/2024 academic year. The study's novelty lies in its exploration of parental satisfaction in the digital era and rapid technological development, integrating parents' expectations for technology use in early childhood education. The findings of this research are expected to provide valuable insights for PAUD institutions in improving their educational services and for policymakers to support the development of early childhood education in the region. The research also contributes to the academic literature by offering a new perspective on customer satisfaction in the context of early childhood education.